Antioxidant Activity and Estimation of Quercetin from Methanolic Extract of Euphorbia nerifolia Leaves by RP-HPLC - Pattanaik, Sovan; Adhikari, Lopamudra; Ghosh, Goutam; Chandra Si, Sudam; Shankar Nayak, Siva (Asian Journal of Chemistry, 2015)
The present study was designed to investigate the antioxidant activity of methanolic extract of Euphorbia nerifolia leaves and its column fractions followed by identification and quantification of the quercetin by using RP-HPLC technique in the effective fraction. The phenolic and flavonoid contents in the crude methanolic extract and its fractions are in the order of fraction 2 (F2) > methanolic extract (ME) > fraction 3 (F3) > fraction 1 (F1). The fraction 2 of methanolic extract of Euphorbia nerifolia leaves showed moderate free radical scavenging activity as evidenced by IC50 values in DPPH (65.4 μg/mL) and ABTS (64 μg/mL) scavenging assays. The chromatogram of fraction 2 was found to be almost the same peak eluted at 3 min same as that of the standard quercetin. In the present study, a rapid RP-HPLC method was suitable for the standardization of herbal extracts for the estimation of quercetin and the results of antioxidant study may have implication in the use of quercetin as a therapeutic agent in the prevention of oxidative stress related diseases.